THE UNBEARABLE HEAVINESS OF TRAUMA - Hayes, Grahame (PINS-Psychology in Society, 2025)
Levy, S and Lemma, A (eds) (2004) The perversion of loss: Psychoanalytic perspectives on trauma. London: Whurr Publishers. ISBN 1 86156 433 3. xviii + 172 Pages. The notion of trauma is the stock-in-trade of psychoanalytic explanations of neurosis. It is also the conceptual origin of Freud’s early psychological account of his first female patients’ symptoms of hysteria (cf Breuer & Freud, 1974). As we all recall from classical psychoanalytic theory, trauma (or traumatic events and experiences) produces anxiety around which defences are rallied resulting in the formation of neurosis. Freud’s (1940) view was that all neuroses were the result of infantile traumata, and consequently he had more to say about the early vicissitudes of psychosexual development than the traumas that befall us as adults (with the exception of war neurosis or “shell shock”). And yet there is something extraordinarily tame about the “normal” psychosexual traumata of neurosis compared to the mostly horrific traumatic events discussed in Levy and Lemma’s The perversion of loss. The perversion could as easily apply to the violation of humanity that people inflict on each other, politically, socially, and interpersonally.